PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 4 SUTERA KABUPATEN PESISIR SELATAN - Jasman, Alandri; Yunita, Alfi; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTThe background of this research is because the low understanding in mathematics of VII grade students of SMP Negeri 4 sutera. The purpose of this study was to determine how the development of students understanding of concepts during the learning of mathematics with a âBisnis Berisikoâ with quis and find out if the students understanding of mathematical concepts Junior High School VII SMP 4 Sutera that uses techniquesâ Bisnis Berisikoâ Quiz with a better understanding of the mathematical concepts students with conventional teaching junior High School VII SMP 4 Sutera. This is the kind of experiment research, with the subject random. The population of this research is all of VII grade students SMP Negeri 4 sutera that consists of and clasres. The sample is taken randomly and VII.1 as a experiment class and VII.2 as a control class. The instrument of this research is the quizzes to check progress of students concepts and find test with indicator consept understanding and sclaring based on analytic ârubricâ. The form of test is a essay concept with reliable test Â is 0,873. The analysis data used is the test of t with MINITAB software. Based of result in analysis data found that two sample classes are distributed normally and having the homogeny variation in a level 95%. The hypothesis testing find P-value = 0,006 and itâs smaller than at Â = 0,05. So, itâs can concluded that the studentâs concepts understanding by using âBisnis Berisikoâ technique is better than the conventional learning in VIII grade students of SMP Negeri 4 sutera.